Nematode infection in the lizard Bogertia lutzae (Loveridge, 1941) from the Atlantic forest in north-eastern Brazil - Avila, R. W. [UNESP]; Anjos, L. A. [UNESP]; Goncalves, U.; Freire, E. M. X.; Almeida, W. O.; da Silva, R. J. [UNESP] (Cambridge University Press, 2010)
Endoparasites associated with the small bromelicolous lizard Bogertia lutzae, a poorly studied phyllodactylid inhabitant of north-eastern Brazil, were studied. Fifty-seven specimens collected from the Atlantic Forest of Alagoas state were dissected. Only one species of parasite, the nematode Spauligodon oxkutzcabiensis, was found, with a prevalence of 22.8%. The intensity of infection was 2.62 +/- 1.19, and neither the prevalence nor mean intensity differed between the sexes. There was no correlation between lizard body size and intensity of infection. An aggregated pattern of distribution (D = 0.813) of S. oxkutzcabiensis was found in this lizard host population. Bogertia lutzae represents a new host recorded for S. oxkutzcabiensis, a parasite reported for the first time for Brazil.